Peningkatan Kesadaran Lingkungan melalui Edukasi Dini mengenai Lingkungan Laut dan Perubahan Iklim bagi Siswa SMAN 1 Moyo Utara, Kabupaten Sumbawa - Astriana, Baiq Hilda; Putra, Aryan Perdana; Arlina, Baiq Fadila (Universitas Mataram, 2024)
One of the environmental issues currently in the global spotlight is climate change. The marine environment is among the most affected by climate change. Various efforts are being undertaken by governments, NGOs, and other environmental organizations to reduce the factors causing environmental change. However, full community involvement remains challenging due to a lack of environmental awareness. Early education offers a potential solution to increase public awareness, for example, through educating student groups. The purpose of this program is to provide students with insights into climate change, its impact on the marine environment, and preventive measures. The method used involves delivering relevant materials to the participants. The participants include 60 students from SMAN 1 Moyo Utara, Sumbawa Regency. An evaluation was conducted by giving pre-test and post-test for the participants resulting in the increase of participants’ knowledge of 81-205%. As a result of this activity, students gained more knowledge about the impacts of climate change on the marine environment, and their awareness of participating in environmental conservation efforts began to grow.